The Needs Of Bullying Prevention Model Based On Sunnah Nabawiyyah - Amran Abdul Halim; Ahmad Sanusi Azmi; Norazmi Anas; Shahril Nizam Zulkipli; Abdul Halim Remly; Mohd Ahsani A. Malek; Ishak Suliaman; Anaztasia Natasha Muhamad Ramlan (Human Resource Management Academic Research Society, 2024)
Indexed by ERA